2011
DOI: 10.1158/1535-7163.mct-11-0424
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E δ-Tocotrienol Augments the Antitumor Activity of Gemcitabine and Suppresses Constitutive NF-κB Activation in Pancreatic Cancer

Abstract: The nuclear factor-κB (NF-κB) transcription factor functions as a crucial regulator of cell survival and chemoresistance in pancreatic cancer. Recent studies suggest that tocotrienols, which are the unsaturated forms of vitamin E, are a promising class of anti-cancer compounds that inhibit the growth and survival of many cancer cells, including pancreatic cancer. Here, we show that tocotrienols inhibited NF-κB activity and the survival of human pancreatic cancer cells in vitro and in vivo. Importantly, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
116
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(144 citation statements)
references
References 19 publications
(24 reference statements)
8
116
0
1
Order By: Relevance
“…One intriguing finding that has been demonstrated consistently by us and others is the selective killing effect of VEDT against cancer cells (12, 14, 32, 33). We have also demonstrated selective induction of apoptosis by VEDT of pancreatic transformed and malignant epithelial cells but not normal immortalized human pancreatic ductal epithelial cells (12, 32). Other anticancer effects of tocotrienol include the inhibition of cell migration and invasion and the inhibition of angiogenesis (21, 24, 34).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…One intriguing finding that has been demonstrated consistently by us and others is the selective killing effect of VEDT against cancer cells (12, 14, 32, 33). We have also demonstrated selective induction of apoptosis by VEDT of pancreatic transformed and malignant epithelial cells but not normal immortalized human pancreatic ductal epithelial cells (12, 32). Other anticancer effects of tocotrienol include the inhibition of cell migration and invasion and the inhibition of angiogenesis (21, 24, 34).…”
Section: Discussionsupporting
confidence: 59%
“…Earlier studies have shown in vitro using pancreatic cancer cell lines and in vivo using a xenograft mouse model and conditional Kras G12D mouse model that VEDT inhibits cell survival, including oncogenic Kras signaling (12, 14, 2628). Here, we investigated the effect of VEDT on Kras signaling and cell cycle proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin (diferuloylmethane), a derivative of the spice turmeric, potentiates the chemosensitivity of gemcitabine by inhibiting IκBα phosphorylation [43]. Meanwhile, tocotrienols, naturally occurring unsaturated vitamin E compounds, augment the antitumor activity of gemcitabine by suppressing the phosphorylation of IκBα [44]. Honokiol, a biologically active biphenolic compound isolated from Magnolia officinalis/grandiflora, also potentiates the cytotoxicity of gemcitabine by inducing G1-phase cell cycle arrest and suppressing IκBα phosphorylation [45].…”
Section: Introductionmentioning
confidence: 99%